Analisis Kelayakan Usaha Pembibitan Jeruk Siem Banjar (Citrus Suhuensis Tan.) Secara Okulasi Di Kota Banjarbaru Provinsi Kalimantan Selatan - Ilhamiyah ilhamiyah; Khairun Nimah; Sunarwo Sunarwo (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2014)
This study aims to determine the citrus nursery business in siem banjar Banjarbaru City of grafting on the economic aspects, namely cost, revenue, profit, and the feasibility of the breakeven point. This study used a survey method. Sources of data in this study were obtained from the primary data and secondary data. Method of data collection in census., Who were respondents in this study were all citrus seed breeder in grafting siem banjar Banjarbaru City totaling 19 breeder. The results of the study in the production period is as follows: 1) Costs incurred an average of Rp 21,734,273.50 / breeder (equivalent to Rp 314,338,666.32 / ha.; 2) Gained revenue breeder average of Rp 37,378,684.21 / breeder (equivalent to Rp 540,600,804.69 / ha.; 3) Gains profit by breeders during the production period by an average of Rp 15,644,410.71 / breeder (equivalent to Rp 226,262,138.43 / ha); 4) Feasibility RCR value or an average of 1.72 which means worthy to be pursued.; 5) Breakeven point on citrus breeding siem Banjar in grafting is Rp 2063.72.